2016
DOI: 10.18632/oncotarget.12876
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic efficacy of the bromodomain inhibitor OTX015/MK-8628 in ALK-positive anaplastic large cell lymphoma: an alternative modality to overcome resistant phenotypes

Abstract: Anaplastic large cell lymphomas (ALCL) represent a peripheral T-cell lymphoma subgroup, stratified based on the presence or absence of anaplastic lymphoma kinase (ALK) chimeras. Although ALK-positive ALCLs have a more favorable outcome than ALK-negative ALCL, refractory and/or relapsed forms are common and novel treatments are needed. Here we investigated the therapeutic potential of a novel bromodomain inhibitor, OTX015/MK-8628 in ALK-positive ALCLs.The effects of OTX015 on a panel of ALK+ ALCL cell lines was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Thus far, only an isocorydine derivative (d-ICD) or BETis have been demonstrated to hamper the expression of IGF2BP3 (19,39,49). Here, we provide evidence that the BETi JQ1, which has marked antitumor activity against several hematologic malignancies as well as solid tumors including Ewing sarcoma (41,53,54), decreases the expression of IGF2BP3 and some of its targets (ABCF1, ABCG2, CD44, MMP9) and suppressed the capacity of growth of Ewing sarcoma cells under anchorage-independent conditions. BET proteins are major epigenetic players, connecting chromatin structures with gene expression changes.…”
Section: Discussionmentioning
confidence: 82%
“…Thus far, only an isocorydine derivative (d-ICD) or BETis have been demonstrated to hamper the expression of IGF2BP3 (19,39,49). Here, we provide evidence that the BETi JQ1, which has marked antitumor activity against several hematologic malignancies as well as solid tumors including Ewing sarcoma (41,53,54), decreases the expression of IGF2BP3 and some of its targets (ABCF1, ABCG2, CD44, MMP9) and suppressed the capacity of growth of Ewing sarcoma cells under anchorage-independent conditions. BET proteins are major epigenetic players, connecting chromatin structures with gene expression changes.…”
Section: Discussionmentioning
confidence: 82%
“…Numerous studies have shown that c-MYC is essential for multiple myeloma cell survival and that IRF4 regulates its expression [ 37 ]. Moreover, it has been recently demonstrated that IRF4 and MYC signaling play an essential role ALCL cell lines survival [ 38 ] and that the treatment with BET family inhibitors may have a therapeutic efficacy in ALK positive ALCL [ 39 ]. Therefore, we tested whether the combination of pomalidomide with the BET family inhibitor JQ1, which inhibits MYC and IRF4 expression, could sensitize ALCL cells to IMiDs treatment.…”
Section: Resultsmentioning
confidence: 99%
“…It has been recently demonstrated that IRF4 and MYC signaling play an essential role ALCL cell lines survival [ 38 , 39 ]. Interestingly, the possibility of combinatorial block of MYC and IRF4 gene expression was greatly advanced by the demonstration that treatment of multiple myeloma tumor cells with the BET-bromodomain inhibitor JQ1 led to loss of BRD4 at super-enhancers, and consequent transcription elongation defects of genes with super-enhancers, including MYC and IFR4 [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bromodomain and extraterminal domain (BET) inhibitors represent a promising group of therapeutics that inhibit YAP/p21/MYC signaling, MYC and IRF4 expression, and the E2F and mTORC pathways. [46][47][48] Because MYC, E2F, and mTORC represented the top gene sets associated with MSC E116K overexpression by GSEA, we in Karpas 299 cells, followed by mass spectrometry, revealed similar musculin:E-protein interactions. There was a slightly increased interaction between MSC E116K and E2A isoforms, although none of the differences was statistically significant.…”
Section: Potential Therapeutic Targeting Of Alcls With Msc E116kmentioning
confidence: 94%